Introduction - Frankfurter, David 1961- (2019)
This chapter justifies the etic (theoretical) parameters of emic (indigenous/textual) discourses of ambiguous, unsanctioned, or illegitimate ritual before discussing comparatively the various preoccupations of such discourses in the ancient world, as analyzed in Part 2.